PV Grid-connected Control Strategy Based on Instantaneous Power Theory - HAN Mengmeng; LI Hongsheng; LI Nan; FAN Yun; GUO Yong (Kongzhi Yu Xinxi Jishu)
Based on the instantaneous power theory, a control strategy of photovoltaic grid connected with APF (active power filter) was studied. This control strategy not only can realize harmonic and reactive current real-time dynamic tracking and compensation of nonlinear load without phase locked circuit, but also can transmit the maximum active power in real-time from photovoltaic to power grid, with the advantages of simplified circuit, cost saving and stable DC side capacitor voltage. Matlab/Simulunk simulation results show that the control theory is correct, and can achieve the goal of improving efficiency of photovoltaic power generation and power quality of power grid.